Hepatitis B Virus Serum DNA andRNA Levels in Nucleos(t)ide Analog‐Treated or Untreated Patients During Chronic and Acute Infection. Issue 6 (22nd September 2018) - Butler, Emily K.; Gersch, Jeffrey; McNamara, Anne; Luk, Ka‐Cheung; Holzmayer, Vera; de Medina, Maria; Schiff, Eugene; Kuhns, Mary; Cloherty, Gavin A.
Abstract : Treatment of chronic hepatitis B (CHB) patients with nucleos(t)ide analogs (NAs) suppresses hepatitis B virus (HBV) DNA synthesis but does not affect synthesis of HBV pregenomic RNA (pgRNA). Hepatitis B virus pgRNA is detectable in the serum during NA treatment and has been proposed as a marker of HBV covalently closed circular DNA activity within the infected hepatocyte. We developed an automated assay for the quantification of serum HBV pgRNA using a dual‐target real‐time quantitative PCR approach on the Abbott m 2000 sp/rt system. We demonstrate accurate detection and quantification of serum HBV RNA. Hepatitis B virus DNA was quantified using the Abbott RealTi m e HBV viral load assay. We further compared serum nucleic acid levels and kinetics in HBV‐positive populations. Samples included on‐therapy CHB samples (n = 16), samples (n = 89) from 10 treatment naïve CHB subjects receiving 12 weeks of NA treatment with 8‐week follow‐up, hepatitis B surface antigen–positive blood donor samples (n = 102), and three seroconversion series from plasmapheresis donors (n = 79 samples). Conclusion : During NA treatment of CHB subjects, we observed low correlation of HBV DNA to pgRNA levels; pgRNA concentration was generally higher than HBV DNA concentrations. In contrast, when NA treatment was absent we observed serum pgRNA at concentrations that correlated to HBV DNA and were approximately 2 log lower than HBV DNA. Importantly, we observe this trend in untreated subject samples from both chronic infections and throughout seroconversion during acute infection. Results demonstrate that the presence of pgRNA in serum is part of the HBV lifecycle; constant relative detection of pgRNA and HBV DNA in the serum is suggestive of a linked mechanism for egress for HBV DNA or pgRNA containing virions.